Решите уравнение  1)  (3x+5)^2- (2x+5)^2= 0   2)  (2x-1)^1- (x-2)^2=0  

Решите уравнение  1)  (3x+5)^2- (2x+5)^2= 0   2)  (2x-1)^1- (x-2)^2=0  
Гость
Ответ(ы) на вопрос:
Гость
1)9x^2+30x+25-(4x^2+20x+25)=5x^2+10x; 5x^2+10x=0 x(5x+10)=0 x1=0 или 5x=-10                    x=-2 2)4x^2-4x+1-(x^2-4x+4)=3x^2-3; 3x^2-3=0; x^2=1 x1=1 или х2=-1  
Гость
1)  (3x+5)^2- (2x+5)^2= 0         (3x+5-2x-5) (3x+5+2x+5) =0        x (5x+10)= 0       x=0    или     5х+10 =0                               5(х+ 2) =0                              х=-2 Ответ: 0, -2 2)  (2x-1)^2-(x-2)^2=0       (2х-1-х+2) (2х-1+х-2) = 0      (х+1) (3х-3) =0       х+1= 0    или    3х-3=0        х=-1                  2(х-1) =0                                   х=1 Ответ: -1, 1                                 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы